(untitled) (Latakia University Journal -Biological Sciences Series, 2022)
This study aimed to study microbial contamination and its relationship with chemical contamination with two heavy metals (lead and cadmium) in news marine sediments at three sites from the beach of Lattakia city during the summer of 2021 and the effect of some hydrochemical properties of marine water in previous parameters. The results showed that the concentrations of lead (25.43 - 41.69 mg/kg) and cadmium (1.37-3.14) were correlated with Bacterial total count, Fecal Coliform and Fecal Streptococcus density in recent marine sediments from several stations located along the beach of Lattakia city during the summer of 2021. The results showed a clear effect of each of the hydrochemical factors (salinity, pH, temperature and concentration of organic matter) and biological factors (Bacterial total count, Fecal Coliform and Fecal Streptococcus) on the concentrations of heavy metal elements studied. A clear rise in the studied heavy metal elements and bacterial indicators of fecal contamination were observed in the stations of the Saqia Musa and the Al-Kabeer Al-Shamali estuary affected by sewage, agricultural and industrial wastewater and compared with the stations of the Sports City site, which is relatively far from the sources of pollution. Key words: New coastal sediments, heavy metals, bacterial pollution.